2007
DOI: 10.1902/jop.2007.060216
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Enzyme Levels After Scaling and Interleukin‐1 Genotypes in Japanese Patients With Chronic Periodontitis

Abstract: These results documented that salivary AST, ALT, and LDH levels reflect inflammation and destruction of periodontal tissue, suggesting clinically useful markers following periodontal therapy. In addition, although IL-1A+4845 alleles may not influence clinical parameters, they may influence post-scaling values of salivary AST and ALT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 25 publications
3
41
0
Order By: Relevance
“…Statistical analysis comparing between the ALP activity of the three groups of this study revealed a significant difference [P˂ 0.05] between control and gingivitis as the ALP activity increase in gingivitis. This result agree with many results from other studies as in Yoshie et al [24] that showed an increase in the alkaline phosphatase activity in the severe stage of periodontal diseases, and after treatment, the activity of this enzyme was restored to the normal value found in healthy persons. There are some suggestions to explain this increase.…”
Section: Resultssupporting
confidence: 93%
“…Statistical analysis comparing between the ALP activity of the three groups of this study revealed a significant difference [P˂ 0.05] between control and gingivitis as the ALP activity increase in gingivitis. This result agree with many results from other studies as in Yoshie et al [24] that showed an increase in the alkaline phosphatase activity in the severe stage of periodontal diseases, and after treatment, the activity of this enzyme was restored to the normal value found in healthy persons. There are some suggestions to explain this increase.…”
Section: Resultssupporting
confidence: 93%
“…1 Alkaline phosphatase (ALP) is an intracellular enzyme present in the saliva and most tissues, organs and bones, including the epithelial, inflammatory cells, bacterial organisms and mineralising tissue cells. [3][4][5] The enzyme is related to cell injury and death. ALP most commonly correlates with bone metabolism and is present in the osteoblast cell membrane and polymorphonuclear leukocyte granules.…”
mentioning
confidence: 99%
“…3 Destructive processes in the alveolar bone can lead to increased ALP activity. 4,5 A key factor in enzyme functionality is pH, with the optimum pH for ALP activity being ≈ 7.4. 6 Therefore, the maximum enzyme activity of ALP is related to the pH and concentration of phosphate esters existing in cells.…”
mentioning
confidence: 99%
“…Each sample thus collected was centrifuged at 3,000 rpm for 5 min at 4ºC. All the samples were collected in the order described above and then immediately sent to a medical examination laboratory (BML Corporation, Tokyo, Japan) for bacterial analysis (7)(8)(9)12).…”
Section: Sample Collectionmentioning
confidence: 99%
“…Quantitative analysis of periodontal bacteria in clinical specimens, such as saliva, supragingival plaque and subgingival plaque, is important for diagnosis, evaluation, and risk assessment of patients with periodontal disease or who are prone to it. Using real-time PCR methods (5-7), clinicians can easily evaluate these periodontal bacteria and their association with clinical symptoms (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%